CORRELATION OF HANDWASHING AND BASIC HOUSEHOLD SANITATION TOWARDS NUTRITIONAL STATUS OF TODDLER (UNDER 2 YEARS OLD/ BADUTA) IN BOJONEGORO DISTRICT - Haibah, Anizah Izzi (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2022)
ABSTRACTBackground: Nutrition problems in toddlers are still a significant problem both on a global and local scale. Intensive monitoring of nutritional status and controlling various factors related to nutritional status is very important to be done especially in the critical period that is before the child is two years old (Toddler/Baduta). Objective: Analyze the relationship of mother/main caregiver's handwashing and basic household sanitation with the nutritional status of Toddler (under two years old/Baduta) in Mojosari Village, Bojonegoro. Method: This research was a descriptive-analytic with a crosssectional design with the target is the entire population of Toddler (under two years old) that meets the inclusion and exclusion criteria. Data collection was done by questionnaire and observation. Relationship analysis was performed with fisher exact test. Result : This study did not find any significant relationship between hand washing (p = 1 > α (0.05)) and basic household sanitation (p = 0.2485 > α (0.05)) with nutritional status. Conclusion: The absence of significant relationships that was found in this study was due to the presence of other complex variables related to nutritional status. ABSTRAK Latar belakang : Permasalahan gizi pada balita masih menjadi masalah yang signifikan baik pada skala global maupun lokal. Pemantauan intensif terhadap status gizi serta pengendalian berbagai faktor yang berhubungan dengan status gizi merupakan hal yang sangat penting untuk dilakukan terutama pada periode kritis yaitu sebelum anak berusia dua tahun (Baduta). Tujuan : Menganalisis hubungan kebiasaan cuci tangan ibu/pengasuh utama dan sanitasi dasar rumah dengan status gizi pada Toddlerdi Desa Mojosari, Bojonegoro. Metode : Penelitian ini adalah deskriptif analitik dengan desain cross sectional yang sasarannya adalah seluruh populasi Toddleryang memenuhi kriteria inklusi dan eksklusi. Pengumpulan data dilakukan dengan kuesioner dan observasi. Analisis hubungan dilakukan dengan uji fisher exact. Hasil : Penelitiaan ini tidak menemukan adanya hubungan yang signifikan antara kebiasaan cuci tangan (p =1 > α (0,05)) dan sanitasi dasar rumah (p = 0,2485 > α (0,05)) dengan status gizi. Kesimpulan : Tidak adanya hubungan yang ditemukan pada penelitian dikarenakan adanya variabel kompleks lainnya yang berhubungan dengan status gizi.